Analysis of Urban Drainage System: (Darmo Satellite Channel Case Study) Surabaya City - Wahyu Joko Pramono; Adi Prawito (Journal of World Conference (JWC), 2022)
rainage channel designed to accommodate plans with precipitation data, safe based on the use of, land and the dimensions. channelDrainage channel in water catchment areas along a channel darmo satellite is one of infrastructures supporting functioning of an urban system in the city surabaya.Changes in land over the function of the green space into land settlement and trade services responsible for the runoff of the surface in several locations in the city of surabaya. The problem a runoff a surface that often happens when the rainy season resulting from increased discharge of water drainage channel water catchment areas in the rain along a channel darmo, satellite causing the need for a study to analyze the performance of drainage channel. The data used in this study is secondary data, namely: the last 10 years of rainfall data obtained from rain stations (gunungsari rain stations, simo, and cages) and drainage channel data. While the methods used are hydrological analysis, arithmetic methods, and gumble methods. The data obtained is then analyzed to find out the plan discharge and drainage channel capacity. The analysis conducted in this study includes hydrological and hydraulic analysis. Hydrological analysis includes: 1) calculation of planned rainfall with Gumbel distribution with a re-period of two and five years, and 2) calculation of plan discharge using HSS Nakayasu.